Índice neutrófilolinfocito como predictor de sepsis neonatal temprana. Hospital Carlos Andrade Marín, 2021 - Jacho Loachamin, Alexis David (2022)
ABSTRACT: The present work, named Neutrophil-lymphocyte index as a predictor of early neonatal sepsis. Hospital Carlos Andrade Marín, 2021, aims to determine the relationship between the neutrophil/lymphocyte index values with early neonatal sepsis, assessing it as a predictor of it. Deaths in the first 28 days of life are now known to be due to various disorders and diseases including unnecessary therapy or non-treatment immediately after delivery for infectious diseases, the incidence of neonatal sepsis in developing countries is still higher than in developed countries. This is why it is of paramount importance to know and question easily accessible tools or tests that substantially reduce neonatal morbidity and mortality. This is an analytical, observational, cross-sectional study because all the data will be obtained from the review of the medical records in the AS400 system of the Hospital de Especialidades Carlos Andrade Marin, with a sample of 135 newborns with a diagnosis of suspected neonatal sepsis or neonatal clinical sepsis, at a given time stage that met the selection criteria and was not considered data after or before the study. Data analysis was performed via SPSS version 25. ROC curve analysis was applied to calculate specificity and optimal sensitivity for values of the neutrophil-lymphocyte index and blood culture, as well as the calculation of the Kappa coefficient to measure diagnostic concordance PCR and INL. To evaluate the presence or not of a relationship between blood culture and the neutrophil/lymphocyte ratio, statistical significance tests were performed using the SPSS program, such as Chi², to interpret the direction and intensity of the relationship between the two variables. The results obtained did not show a statistically significant association (p<0.05) between blood culture and INL, giving a Chi² value of p = 0.433, while the calculation of the kappa coefficient gives a moderate diagnostic agreement between INL and CRP.